Quality of life of mastectomized women undergoing immediate breast reconstruction in a cancer referral hospital in Amazonas: a cross-sectional study - Roberto Alves Pereira; Hilka Flavia Barra do Espírito Santo Alves Pereira; Gabriel Pacífico Seabra Nunes; Edson De Oliveira Andrade; Valbécia Tavares de Aguiar (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: The assessment of the quality of life is considered important for a more humanistic and comprehensive treatment approach. Methods: This is a descriptive cross-sectional observational study using a quantitative approach. The quality of life of women undergoing immediate breast reconstruction after mastectomy at the Amazonas Oncology Control Center Foundation (Centro de Controle de Oncologia do Amazonas) from January to June 2015 was assessed. The assessment instrument used was the WHOQOL-BREF questionnaire, following the syntax of the WHOQOL Group. Results: The sociodemographic profiles of 22 patients were evaluated. The predominant age group was 45-49 years, the predominant educational level was high school (63.64%), 90.91% of the patients were from Manaus, and 72.73% were married. A total of 41% of the respondents defined their quality of life as good in the questionnaire, with the physical domain being the most affected and the social relationships domain being the less affected. Conclusion: The assessment of the quality of life should be prioritized in the choice of treatment for breast cancer.